IMPLEMENTASI INTEGRASI SEKTORAL PROGRAM KEBIJAKAN REHABILITASI ACEH SINGKIL PASCA BENCANA - Soesilowati, Etty (JEJAK: Jurnal Ekonomi dan Kebijakan, 2010)
The research aimed to synchronize inters sectors, which uses Rencana Tata Ruang dan Wilayah Â as main guide. Scope of the discussion consist of comparison between the exixting and should condition. The locus of this research was in direct Aceh Singkil by focusing on housing and settlement, business and post disater infrastructure. The secondary data resources collected from BRR (Badan Rekonstruksi dan Rehabilitasi), The local Government of province and county and the identified funding institution. The primary data resources collected from interview, observation, focus group discussion and stakeholders meeting forum. The data analyzed by participative planning analysis, policy analysis, scale of priority and budget analysis. The result of this research showed: (1) there was overlapping program found on housing and settlement sectors; (2) some program that should be required but in fact they didnât appear, even In infrastructure, housing and settlement sector and economics; (3) most of the program proposed to BRR expected to get financial support from BRR. The recommendations are: (1) they should organize completely definite RTRW program includes the amount of budget needed for the coming 20 years; (2 )they should allocate the budget for maximum 40% of APBD for routine and 60% for development, because after year of 2009 BRR and NGOâs will be no longer work there; (3) the patterns of coordination should gradually do from Musrenbang/Musbangdes/Musbang to sub district/county and another communication forum. Â